Initial Characterization of the Viridisins’ Biological Properties - Vermeulen, Ross Rayne; van Staden, Anton Du Preez; Ollewagen, Tracey; van Zyl, Leonardo Joaquim; Luo, Youran; van der Donk, Wilfred A.; Dicks, Leon Milner Theodore; Smith, Carine; Trindade, Marla (ACS omega, 2024)
Viridisin A1 and A2 were previously heterologously expressed, purified, and characterized as ribosomally produced and post-translationally modified lanthipeptides. Such lanthipeptide operons are surprisingly common in Gram-negative bacteria, although their expression seems to be predominantly cryptic under laboratory conditions. However, the bioactivity and biological role of most lanthipeptide operons originating from marine-associated Pseudomonadota, such asThalassomonas viridans XOM25T, have not been described. Therefore, marine-associated Gram-negative lanthipeptide operons represent an untapped resource for novel structures, biochemistries, and bioactivities. Here, the upscaled production of viridisin A1 and A2 was performed for (methyl)lanthionine stereochemistry characterization, antibacterial, antifungal, and larval zebrafish behavioral screening. While antimicrobial activity was not observed, the VirBC modification machinery was found to install both dl- and ll-lanthionine stereoisomers. The VdsA1 and VdsA2 peptides induced sedative and stimulatory effects in zebrafish larvae, respectively, which is a bioactivity not previously reported from lanthipeptides. When combined, VdsA1 and VdsA2 counteracted the sedative and stimulatory effects observed when used individually.